Ultrasound assessment of the spring ligament and posterior tibial tendon in healthy subjects: A descriptive study - Lópezosa-Reca, Eva; Vallejo Marquez, Mercedes; Fornells, Salvador; Martinez-Franco, Alfonso; Tejero, Sergio (Elsevier, 2024)
Background: The main aim of this study was to ultrasonographically analyse the thickness and the relationship between the Superomedial Bundle of the Spring Ligament and the Posterior Tibial Tendon in healthy subjects and its relationship with different epidemiological variables. Methods: Fifty-five healthy feet with a mean of 47 years old measuring the same ultrasound model and researcher. Demographic variables (age, sex, laterality, BMI, type of sports activity performed, and type of work activity) were collected from all participants. The thickness of the PTT and the Spring Ligament was measured in both longitudinal and transverse diameters. The intraclass correlation coefficient (ICC) was also analysed to assess the agreement of the measurements between a researcher and the ultrasound specialist radiologist. Results: The mean thickness of the Spring ligament was 5.07 mm (95 % CI 4.75-5.38), while that of the PTT in its long axis was 3.58 mm (95 % CI 3.37-3.79). Regarding the interobserver agreement analysis, the intraclass correlation coefficient for measurements between observers was 0.91 (CI95 %: 0.698-0.977) which denotes a high degree of similarity between the clinician and the radiologist. Conclusion: This study describes the relationships between the thickness of the posterior tibial tendon and the superomedial Bundle of the Spring ligament in healthy subjects, as well as their variability according to certain epidemiological variables such as age, gender, occupation, and sport. On the other hand, the measurements taken by a researcher high agreement with those taken by a radiologist specialized in ultrasound.
Keywords: Tendones; Ligamentos; Flatfoot; Posterior tibial tendon; Spring ligament; Ultrasound.; Flatfoot; Ultrasound; Spring ligament; Posterior tibial tendon